Photoelectron Spectroscopy and Ionic Fragmentation of OSeCl2 and Its Analogue OSCl2 under VUV Irradiation - Gerones, Mariana (2015)
The electronic structure and the dissociative ionization of selenium oxychloride, OSeCl2, have been investigated in the valence region by using results from both photoelectron spectroscopy (PES) and synchrotron-based photoelectron photoion coincidence (PEPICO) spectra. The PES is assigned with the help of quantum chemical calculations at the outer-valence Green's function (OVGF) and symmetry adapted cluster/configuration interaction (SAC-CI) levels. The first energy ionization is observed at 11.47 eV assigned to the ionization of electrons formally delocalized over the Se, Cl, and O lone pair orbitals. Irradiation of OSeCl2 with photons in the valence region leads to the formation of OSeCl2•+, OSeCl+, SeCl2•+, SeCl+, and SeO•+ ions. Furthermore, the inner shell Se 3p, Cl 2p, and Se 3s electronic regions of OSeCl2 together with S 2p, Cl 2p, and S 2s electronic regions of thionyl chloride, OSCl2, have been studied by using tunable synchrotron radiation. Thus, total ion yield spectra and the fragmentation patterns deduced from PEPICO spectra at the various excitation energies have been studied. Cl+, O•+, and Se•+ ions appear as the most intense fragments in the OSeCl2 PEPICO spectra, like in the sulfur analogue OSCl2, whose photofragmentation is dominated by the Cl+, O•+, and S•+ ions. Fragmentation processes in OSCl2 leading to the formation of the double coincidences involving atomic ions appear as the most intense in the PEPIPICO spectra. (Figure Presented).